PENERAPAN MANAJEMEN PETANI KENTANG MELALUI PENDEKATAN AGRIBISNIS DI DESA ERELEMBANG KECAMATAN TOMBOLOPAO KABUPATEN GOWA - Rumallang, Ardi (Jurnal Ilmiah Ecosystem, 2019)
This study aims to analyze the application of potato farmer management, farmers' level of production, productivity and income through an agribusiness approach in Erelembang Village, Tombolopao District, Gowa Regency.The population and sample in this study were all potato farmers. The number of samples in this study were 66 people using random sampling techniques. The data used in this study are primary data and secondary data. The analysis used in this study is descriptive qualitative analysis, productivity analysis and income analysis, The results of the study explain that the application of potato farmer management through an agribusiness approach is the application of institutional subsystems, production subsystems, financing subsystems, marketing subsystems, postharvest subsystems and human resource subsystem.